Effects of arbuscular mycorrhizal dominance on taxonomic and phylogenetic beta diversity across vertical strata in a subtropical forest - Yu, Shuisheng; Wu, Qi; Liao, Jianwei; Wang, Xingchen; Ding, Di; Zheng, Rong; Liu, Libin; Chen, Jianhua; Liu, Julian; Wang, Yunquan; Yu, Mingjian (Frontiers in Plant Science, 2025)
Vertical stratification in forests creates important environmental gradients that shape biodiversity patterns. While beta diversity (β-diversity) quantifies community assembly mechanisms, the relative contributions of core ecological processes, specifically biotic interactions, dispersal limitation, and habitat filtering, to taxonomic (TBD) and phylogenetic (PBD) β-diversity across vertical strata remain poorly understood. To address this knowledge gap, we quantified TBD and PBD to disentangle the relative influences of arbuscular mycorrhizal (AM) dominance (as a proxy for biotic interactions), geographic distance (as a proxy for dispersal limitation), and elevation distance (as a proxy for habitat filtering) across four vertically stratified layers (i.e., canopy, subcanopy, shrub, herb layers) in a subtropical forest. We found that species turnover is the primary component of both TBD and PBD across all strata, despite notable variation among layers. Importantly, the relative importance of these drivers on β-diversity components varied significantly across vertical strata. AM fungal dominance exerted increasing influence downward through the strata. Geographic distance became increasingly influential in the lower strata, and was the dominant driver of turnover in the herb layer. Elevation distance persistently influenced turnover components across all strata. Crucially, none of the investigated variables significantly influenced the nestedness components of either TBD or PBD. For PBD specifically, AM fungal dominance accounted for the largest proportion of variation in total PBD within the subcanopy/shrub layers, and significantly influenced specific components (turnover or nestedness) in other layers, while elevation distance exerted a strong influence on components in the subcanopy/shrub layers. However, canopy nestedness and herb-layer turnover of PBD remained decoupled from all drivers. These findings underscore the critical role of vertical stratification and highlight the importance of arbuscular mycorrhizal dominance, a key mechanism shaping community assembly, in elucidating biodiversity maintenance mechanism in structurally complex ecosystems.